The impact of health insurance on health sector indicators in Syria - يوسف علي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to find out the impact of health insurance on the quality of health services provided to individuals by highlighting the role that health insurance plays in improving health sector indicators in Syria and what is positively reflected on the health of the Syrian citizen. Providing him with high-quality health care, focusing on the importance of health insurance and working with all possible means to expand the beneficiaries of this type of insurance to include the largest possible number of citizens. This was done by studying several indicators and conducting a standard analytical study to know the effect of health insurance on these indicators, where it was found that there is a significant effect of health insurance premiums on each of the following (average population for each doctor in Syria, average population for each pharmacist in Syria, life expectancy At birth, the initial death rate per 1000 people), and it was found that there was no significant effect of health insurance premiums on each of the following (average population per dentist in Syria, average population per bed in public and private hospitals, coverage rate with local medicines of the total drug).